Efficacy of sorafenib in patients with gastrointestinal stromal tumors in the third- or fourth-line treatment: A retrospective multicenter experience - DANE, FAYSAL (SPANDIDOS PUBL LTD, 2013)
Sorafenib is a multi-targeted tyrosine kinase receptor inhibitor used to treat patients with advanced gastrointestinal stromal tumors (GISTs). The present study evaluated the efficacy and tolerability of sorafenib therapy for patients with GISTs. Between January 2001 and November 2012, 25 patients, from multiple centers, who had received sorafenib as the third-or fourth-line treatment for GISTs were investigated retrospectively. In total, 17 patients were male and eight were female. The median age was 54.0 years (range, 16-82 years). From the patients, 21 received imatinib for longer than six months and four received it for less than six months. The clinical benefit rate of sorafenib was 40.0%. Treatment-related adverse events were reported in 72% of patients. These adverse events were generally mild to moderate in intensity. The median progression-free survival (PFS) and overall survival (OS) times of the patients who received sorafenib were 7.2 and 15.2 months, respectively. The duration of imatinib usage was an independent prognostic factor for PFS and OS. Sorafenib is an effective treatment in patients with GISTs showing a clinical benefit rate of 40.0% and an acceptable tolerability.
Keywords: sorafenib; gastrointestinal stromal tumors; efficacy; TYROSINE KINASE INHIBITOR; GROWTH-FACTOR; C-KIT; PROGNOSTIC-FACTORS; IMATINIB MESYLATE; IN-VITRO; MUTATIONS; SU11248; SURVIVAL; TAIWANESE